2023
DOI: 10.3390/su151713252
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Pollution: Threats and Impacts on Global Marine Ecosystems

Ren-Shou Yu,
Sher Singh

Abstract: This study investigates the scope of global marine microplastic pollution and its implications on marine ecosystems and human health. We first delve into how plastic enters the ocean, with an emphasis on the accumulation of plastic along coastlines, particularly the formation and impact of the Great Pacific Garbage Patch (GPGP). Through a concentration map of marine microplastics across five continents, the global distribution of microplastic pollution is revealed. Furthermore, the effects of microplastics on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…The pollution generated by marine plastic litter is deemed irreversible and widespread globally, posing threats to ocean health, wildlife, food safety, human health, coastal tourism, and climate regulation [81,82]. This concern arises from the persistence of plastics and their harmful impacts.…”
Section: Potential Impact Of Marine Macro-and Microplastic Littermentioning
confidence: 99%
“…The pollution generated by marine plastic litter is deemed irreversible and widespread globally, posing threats to ocean health, wildlife, food safety, human health, coastal tourism, and climate regulation [81,82]. This concern arises from the persistence of plastics and their harmful impacts.…”
Section: Potential Impact Of Marine Macro-and Microplastic Littermentioning
confidence: 99%
“…PE and PS MPs have been reported that interfere with enzyme synthesis and even alter gene expression [34]. There are also some reports presented that MPs may have a growth-promoting effect on algae due to the strong environmental adaptability of some algae [35]. These previous works show that the toxic mechanism of MPs on algae is a complex process.…”
Section: Introductionmentioning
confidence: 99%
“…Marine ecosystems, currently providing a main source of livelihood for three billion people worldwide (“Ocean economy and developing countries - OECD,” 2023), are under extreme pressure due to a variety of stressors (Pandion et al, 2022), such as current temperature rise (Cheng et al, 2022), biodiversity loss through overexploitation (Ward et al, 2022; Worm et al, 2006), pollution (Datta, 2023; Yu and Singh, 2023) and increased nutrient loads (Howarth et al, 2021; Malone and Newton, 2020). In particular, coastal marine systems and their inhabitants are increasingly affected by climate change and anthropogenic pressures, such as elevated nutrient loads (Breitburg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%